استخدام مؤشر TOI لتقييم تحمل بادرات القمح المعاملة أوليا بالنقع فى محلول ملحى للإجهاد الملحى - عبد القادرد. سعاد أمقدع (Aljameai, 2025)
المستخلص: أجريت تجربة معملية باستخدام تصميم القطاعات الكاملة العشوائية (RCBD) بثلاثة مكررات في معمل قسم التربة والمياه، كلية الزراعة ، جامعة عمر المختار، خلال عام 2024، بهدف دراسة تأثير النقع المسبق لبذور القمح الطرى (Triticum aestivum L.) في محلول ملحى 0.25% لمدة 24 ساعة، على قدرة البادرات على تحمل الإجهاد الملحى. زرعت البذور المنقوعة وغير المنقوعة فى أصص تحتوى تربة طينية مزيجية، وعرضت لأربعة مستويات من الملوحة (0%،1%، 1.5%و2% كلوريد الصوديوم). بعد 30 يوما من الزراعة، تم قياس الوزن الجاف الكلى وحساب مؤشر تحمل الملوحة (TOI). أظهرت النتائج أن النقع المسبق حسن الأداء الفسيولوجى للبادرات، حيث بلغ اعلى متوسط وزن جاف 4.99جم عند مستوى 1.5% NaCl في البذور المنقوعة، مقابل 2.18 جم فى غير المنقوعة. كما انخفضت قيم TOI بوضوح فى النباتات المعاملة مسبقا، إذ سجلت -1.92 مقارنة ب 0.72 فى البذور غير المنقوعة عند نفس المستوى، مما يعكس قدرة أعلى على الحفاظ على الكتلة الحيوية تحت الملوحة. تشير النتائج الى أهمية استخدام مؤشرTOI لتقييم الاستجابة الفسيولوجية المبكرة لتقنية النقع كوسيلة بسيطة واقتصادية فى إدارة الإجهاد الملحى. Abstract: A pot experiment was conducted under controlled laboratory condition at the Department of Soil and Water, Faculty of Agriculture, Omar Al-Mokhtar University, during 2024, using a randomized complete block design (RCBD) with three replicates. The objective was to evaluate the effect of pre-soaking wheat seeds (Triticum aestivum L.) in a 0.25% NaCl solution for 24 hours on salt stress tolerance at the seedling stage. The soaked and unsoaked seeds were sown in clay loam soil pots and subjected to four salinity levels (0% ,1%, 1.5%and 2% NaCl). After 30 days of planting, the total dry weight was recorded, and the salt tolerance index (TOI)was calculated. Results showed that pre-soaking improved the physiological performance of seedlings, with the highest average dry weight of 4.99g recorded at 1.5% NaCl for soaked seeds, compared to 2.18g for unsoaked seeds. TOI values clearly decreased in pre- treated plants, recording -1.29 compared to 0.72 in unsoaked seeds at the same salinity level, indicating a higher ability to maintain biomass under salinity. These findings support the use of TOI as an early physiological indicator for assessing seed priming efficiency under salt stress.